Social- and Health Care Educators’ Cultural Competence - Han R; Koskinen H; Mikkonen K; Sjögren T; Korpi H; Koivula M; Koskimäki M; Lähteenmäki ML; Sormunen M; Saaranen T; Salminen L; Wallin O; et al. (Greece, 2022)
Introduction and aim: Cultural differences have significant impacts on classroom behaviours and communication in teaching. The aim of this study is to explore social and healthcare educators’ cultural competence in transcultural education. Methodology: Data was collected from semi-structured focus group interviews at universities of applied sciences and vocational colleges. Inductive content analysis was used in the analysis process. Results: Educators’ cultural competence in transcultural education emerges as generic categories: transcultural education, educatorship and ethical attitudes, and underpins by the sub-categories: language and linguistics, different learning styles, integrating multicultural students, cultural knowledge and sensitivity, collaborating and cooperating, self-awareness and openness, and respecting and caring. Conclusion: Cultural competence represents a core competence for social-and health care educators. Educators need to know students’ background, master different learning styles, be flexible in their pedagogical approaches and have an open and ethical attitude.